2016
DOI: 10.1103/physreve.93.043109
|View full text |Cite
|
Sign up to set email alerts
|

Regular flow reversals in Rayleigh-Bénard convection in a horizontal magnetic field

Abstract: Magnetohydrodynamic Rayleigh-Bénard convection was studied experimentally using a liquid metal inside a box with a square horizontal cross section and aspect ratio of five. Systematic flow measurements were performed by means of ultrasonic velocity profiling that can capture time variations of instantaneous velocity profiles. Applying a horizontal magnetic field organizes the convective motion into a flow pattern of quasi-two-dimensional rolls arranged parallel to the magnetic field. The number of rolls has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 26 publications
5
35
2
Order By: Relevance
“…3a and 4a); the measured flow magnitude does not change. Previous work dealing with liquid metal convection in the presence of magnetic fields suggest that convection rolls will tend to align with magnetic field lines, producing a more ordered flow structure [114,115]. However, there are two other ways to explain the increase in order much better: electro-vortex flow and internally heated con- vection (IHC).…”
Section: Componentmentioning
confidence: 99%
“…3a and 4a); the measured flow magnitude does not change. Previous work dealing with liquid metal convection in the presence of magnetic fields suggest that convection rolls will tend to align with magnetic field lines, producing a more ordered flow structure [114,115]. However, there are two other ways to explain the increase in order much better: electro-vortex flow and internally heated con- vection (IHC).…”
Section: Componentmentioning
confidence: 99%
“…Various studies have been carried out in the past on RB convection in the presence of a magnetic field (Burr & Müller 2002). A particular interest is RB convection with an applied external horizontal magnetic field (Yanagisawa et al 2013;Tasaka et al 2016). It is observed that under strong magnetic field the convective rolls exhibit quasi-two dimensional flow patterns, which can be understood in terms of linear stability analysis (Tasaka et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A particular interest is RB convection with an applied external horizontal magnetic field (Yanagisawa et al 2013;Tasaka et al 2016). It is observed that under strong magnetic field the convective rolls exhibit quasi-two dimensional flow patterns, which can be understood in terms of linear stability analysis (Tasaka et al 2016). For weak magnetic field, the magnetic damping effect is weak, which causes the convection pattern less coherent and hence losing its quasi-two-dimensional character.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quasistatic limit of small R m is applicable with simplifications of the full set of magnetohydrodynamic equations (Knaepen & Moreau 2008;Davidson 2016). It is actually also the operating point of most laboratory experiments on Rayleigh-Bénard convection (RBC) with external vertical (Cioni et al 2000;Burr & Müller 2001;Aurnou & Olson 2001) or horizontal magnetic fields (Fauve et al 1981;Tasaka et al 2016;Vogt et al 2018). Nakagawa (1955) and Chandrasekhar (1961) showed that a sufficiently strong vertical external magnetic field B 0 can suppress the onset of Rayleigh-Bénard convection.…”
Section: Introductionmentioning
confidence: 99%